Riffaterre's Semiotic Approach to Aḍḍamīru Al-’Arabī Song: Explores Lyrics as a Tool for Arab Integration - Bustam, Betty Mauli Rosa; Naf'an, Abdul Wahab (Diwan : Jurnal Bahasa dan Sastra Arab, 2025)
This study examines the meaning of Arab unity as reflected in the lyrics of the song “Aḍḍamīru al-’Arabī” through the lens of Riffaterre’s semiotic approach. The song was selected due to its powerful symbolism in advocating Arab solidarity. Employing a descriptive qualitative method, the research analyzes the text and context of the lyrics to reveal hidden meanings, ideologies, and symbolic messages. The analysis follows several stages: heuristic and hippogram identification, indirect expression analysis, and retrospective reading. The findings indicate that the song serves not only as a work of art but also as a political instrument in fostering solidarity amidst the Middle East conflict. This study contributes to the field of semiotic analysis and offers a new perspective on the intersection of music and politics within the scope of cultural diplomacy. مستخلص تبحث هذه الدراسة معنى الوحدة العربية كما تتجلى في كلمات أغنية "الضمير العربي" من خلال عدسة المنهج السيميائي لريفاتر. تم اختيار الأغنية بسبب رمزيتها القوية في الدعوة إلى التضامن العربي .باستخدام منهج وصفي نوعي، يحلل البحث نص كلمات الأغاني وسياقها للكشف عن المعاني الخفية والأيديولوجيات والرسائل الرمزية. يستغرق التحليل عدة مراحل: تحديد الاستدلال وتصوير فرس الأنساب، وتحليل التعبير غير المباشر، والقراءة بأثر رجعي. تشير النتائج إلى أن الأغنية لا تعمل كعمل فني فحسب، ولكن أيضا كإداة سياسية لتعزيز التضامن في خضم الصراع في الشرق الأوسط. تساهم هذه الدراسة في مجال التحليل السيميائي وتقدم منظورا جديدا حول تقاطع الموسيقى والسياسة في نطاق الدبلوماسية الثقافية.